Self-Management Counseling Increases Compliance in Diabetes Mellitus Patients - Mulyaningsih, Mulyaningsih; Ardika , Noviana Ayu; Wahyuni, Wahyuni; Hermawati, Hermawati (Jurnal Berita Ilmu Keperawatan, 2025)
People with diabetes mellitus (DM) can experience various complications if they do not have a good lifestyle. People with DM must comply with medication, physical activity, diet, and education to improve a healthy lifestyle. One effort that can be made to improve compliance is to provide Self-Management Counseling (SMC) with the Transtheoretical Model (TTM) approach. This quasi-experimental study involved two groups of DM patients. 79 respondents were selected with the criteria of not having the disease and having diabetes for 2 years. Respondents were divided into an intervention group (40 people) and a control group (39). The results showed that there were differences in compliance with diet (p = 0.001), activity (p = <0.001), treatment (p = <0.001), and education (p = 0.002) between the intervention group and the control group. Therefore, it can be concluded that SMC with the TTM approach has proven effective in improving compliance with type 2 diabetes patients—both compliance with diet, activity, treatment, and education.